The efficacy and safety of gabapentin vs. carbamazepine in patients with primary trigeminal neuralgia: A systematic review and meta-analysis - Zhao, Xin; Ge, Shuyu (Frontiers in Neurology, 2023)
Background: Drug therapy is the most commonly used treatment for primary trigeminal neuralgia (PTN), in which carbamazepine is the the first-line drug. Recently, the anti-epileptic drug gabapentin has also been widely used in patients with PTN, but whether it can be used as a substitute for carbamazepine still needs to be verified. Our study aimed to assess the safety and efficacy of gabapentin versus carbamazepine as treatment for PTN. Methods: We searched seven electronic databases for studies published as of July 31, 2022. All randomized controlled trials (RCTs) of gabapentin versus carbamazepine on PTN patients that met the inclusion criteria were included. Meta-analysis was conducted by using Revman 5.4 and stata 14.0, in which forest plots, funnel plots and sensitivity analysis were performed. Mean difference (MD) and Odds ratio (OR) with 95% confidence intervals (CIs) were used for the measurement indicators of continuous and categorical variables, respectively. Results: Eighteen RCTs with 1604 patients were eventually identified. The meta-analysis showed that compared with the carbamazepine group, the gabapentin group significantly improved the effective rate (OR = 2.02, 95% CI 1.56 to 2.62, P < 0.001), reduced the adverse events rate (OR = 0.28, 95% CI 0.21 to 0.37, P < 0.001), and improved the visual analogue scale (VAS) score (MD = -0.46, 95% CI -0.86 to -0.06, P = 0.03). Although the funnel plot showed evidence of publication bias, the sensitivity analysis revealed the stability of the results. Conclusions: The current evidence showed that gabapentin may be superior to carbamazepine in relation to efficacy and safety in patients with PTN. It is crucial that more RCTs are conducted to confirm the conclusions in the future.